2014
DOI: 10.1210/jc.2014-2670
|View full text |Cite
|
Sign up to set email alerts
|

Successful Mortality Reduction and Control of Comorbidities in Patients With Acromegaly Followed at a Highly Specialized Multidisciplinary Clinic

Abstract: Mortality in acromegaly can be successfully reduced, provided patients are treated using a multimodal approach with careful management of comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
95
2
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(128 citation statements)
references
References 27 publications
17
95
2
14
Order By: Relevance
“…In our cohort, the overall mortality risk was only slightly elevated and in agreement with the literature (2, 3). We recorded an increased mortality from cardiovascular disease but not from cancer, which agrees with a metaanalysis from 2008 (2), although recent surveys from single centres report increased cancer mortality (45) and low prevalence of cardiac disease (46) respectively. Moreover, in a subanalysis, we did not record a significant impact of a given treatment strategy on mortality risk, acute cardiovascular event or chronic complications.…”
Section: Discussionsupporting
confidence: 89%
“…In our cohort, the overall mortality risk was only slightly elevated and in agreement with the literature (2, 3). We recorded an increased mortality from cardiovascular disease but not from cancer, which agrees with a metaanalysis from 2008 (2), although recent surveys from single centres report increased cancer mortality (45) and low prevalence of cardiac disease (46) respectively. Moreover, in a subanalysis, we did not record a significant impact of a given treatment strategy on mortality risk, acute cardiovascular event or chronic complications.…”
Section: Discussionsupporting
confidence: 89%
“…This means that age-related cancer incidence and mortality, previously not clinically apparent in acromegaly, might be unmasked from now on. In agreement with that, two recent studies have shown that mortality in acromegaly can be successfully reduced with current therapies, and in both of them, cancer was the most common cause of death, and it emerged as an independent predictor of mortality (27,33).…”
Section: Aging and Morbiditiessupporting
confidence: 76%
“…However, in two studies (18,32), patients with active disease and persistently elevated GH and IGF1 values had significantly higher mortality from cancer, particularly CRC, than those with normal IGF1 or GH levels, although overall, the cancer-related mortality was not greater than the observed mortality in the general population, and it is not affected by the duration of disease or patient's age at diagnosis (4,10,11). In a recent cohort of 442 patients with acromegaly from a single-center in Mexico City, the standardized mortality ratio (SMR) was similar to that seen in the general population, but among 22 patients who died during the follow-up, cancer was the most common cause of death, and it was a significant predictor of mortality (27). Malignancies were also an independent predictor of mortality in a recent Italian multicenter study with 1512 patients, in which reduction of SMR was linked to the disease control (33).…”
Section: Mortalitymentioning
confidence: 89%
See 1 more Smart Citation
“…The comparison between older and more recent occurrences of the disease is challenging because both cancer incidence in the general population and life expectancy in patients with acromegaly have dramatically changed over the past few decades, influencing the prevalence of disease-associated morbidities. In fact, recent series have found cancer as a common cause of death and an independent predictor of mortality in acromegaly [75][76][77][78]. In addition, population-based cancer registries and epidemiology may vary from site to site.…”
Section: Rycina 2 Dane Epidemiologiczne Wiążące Stężenie Igf-i W Surmentioning
confidence: 99%